Pathogenicity of streptococcus agalactiae in juvenile red tilapia (Oreochromis sp.) from a fish farm in Selangor, Malaysia - Abuseliana, Ali Farag (2011)
Streptococcal infection is one of the emerging bacterial diseases that was reported to cause significant mortality and high economical loss in freshwater and saltwater fish species including Tilapia sp., worldwide. Recently, a streptococcosis outbreak affecting Red tilapia (Oreochromis sp.) farm in Selangor was investigated. Affected fish showed loss of appetite, cornea opacity and serpentine swimming. Healthy and morbid fish were clinically examined. Samples from brain, liver, spleen and kidney were collected for causal agent isolation. Pure bacteria isolates were successfully isolated on trypticase soy agar (TSA) blood agar (BA) and brain heart infusion agar (BHIA). The colonies were of grayish white color, circular, convex, pin-head size and β-haemolytic. All isolates were gram-positive cocci, oxidase-negative and catalase-negative. They were identified as group B Streptococcus agalactiae (GBS) using a commercial identification kit (Streptococcal grouping kit, RapID™ STR System and BBL Crystal GP ID kit). Specific polymerase chain reaction (PCR) and 16S rRNA sequencing technique confirmed the isolates as GBS. The isolates were sensitive to amoxicillin, ampicillin, erythromycin, chloramphenicol, linomycin,rifampicin, vancomycin, gentamicin, sulfamethoxazole + trimethoprime and tetracycline. On contrary, they were resistant to neomycin, amikacin, kanamycin and streptomycin. The 120 hours median lethal dose (LD50) value in juvenile tilapia injected intraperitoneally (IP) was 1.5×105 cfu/mL. Experimental infections were carried out by bathing the fish for 30 minutes in water containing the bacteria and by intraperitoneal (IP) injection. It was observed that IP route was more potent to cause mortality to juvenile Red tilapia and produced clear clinical signs within five days. It was noted that the mortality started to reduce after five days and fish recovered after nine days post inoculation. In contrast, immersion route did not induce mortality, but produced moderate clinical signs such as lethargy and loss of appetite, and fish started to recover after six days. The findings of the current study indicated that S. agalactiae infection started to become an issue in tilapia farms and warrants focusing to formulate a suitable measure to prevent and control the disease before it becomes endemic in the future.